Efecto de la aplicación de diferentes niveles de fertilización edáficos con “Yaramila” sobre el rendimiento de híbridos de maíz, en la zona de Babahoyo - Soto Valle, Piter Yasmany (2013)
Corn is one of the most important agricultural products of the national economy. The province which concentrates most of the corn acreage in Ecuador is Los Ríos with 42% of the total. Production statistics kept close relationship with the area planted. The quintessential coast is the largest producer of corn, however there are also records in production such as the Sierra de Loja and a low percentage in the Amazon. Los Ríos encompasses 49% of total production in 2008 and is best presented average yields 3.3 tm / ha. The objective of this research was to determine the behavior of maize to fertilizer application Yaramila soil to assess its effect on performance. The work was done on the grounds of the experimental farm "San Pablo", located at Km 7.5 of the pathway Babahoyo-Montalvo. Investigated the corn hybrids Pioneer 30F, DK-399 and INIAP-601, with five subtreatments with Yaramila Hydran, Unik, chemical control and farmer. In plots of 20 m2, distributed in a block design completely randomized split plot. For the evaluation of means used the Tukey test at 5% probability. During the crop cycle were evaluated: plant height, ear diameter and ear length, number of ears per plant, days to harvest and to flowering, seed weight, yield per hectare, soil analysis and an economic analysis of the treatments.